Analisis Perbandingan Pendidikan Moderasi Beragama Menurut Yusuf Al-Qaradhawi dan M. Quraish Shihab - Jarkasih Harahap, Ibnu Alwi; Sinaga, Ali Imran; Al Farabi, Mohammad (Kamaya: Jurnal Ilmu Agama, 2025)
Religious Moderation that provides a comprehensive perspective on moderation in the Indonesian context. M. Quraish Shihab’s activeness in writing tafsir works and his moderate attitude in responding to differences among Muslims are added values. This study aims to understand his views on religious moderation and how these values ​​can be applied in education to create harmony amidst diversity. This study uses the library research method, where researchers collect various relevant literature.Religious moderation education is a systematic and holistic process in instilling balanced, inclusive, and contextual Islamic values, which aims to form a tolerant, critical, and humanity-oriented Muslim personality through the integration of prophetic values, rational and spiritual balance, and peaceful national commitment in a pluralistic society. The application of prophetic education in religious moderation, which includes three main values: humanization, liberation, and transcendence. These values ​​are very important in Islamic education because they are able to create individuals who are not only intellectually intelligent, but also have high social and spiritual awareness. Yusuf Al-Qaradhawi defines justice as the peak of moderation, which must be realized in the social and educational systems. Meanwhile, M. Quraish Shihab emphasized that Islam recognizes the needs of humanity and spirituality in a balanced manner. Then the definition of religious moderation education was found which was formulated from several indicators above through the analysis of the two books Kalimat fi al-Wasathiyyah wa Ma’alimuha and Wasathiyah: Islamic insight into religious moderation, namely, “Religious moderation education is a systematic and holistic process in instilling balanced, inclusive, and contextual Islamic values, which aims to form a Muslim personality that is tolerant, critical, and oriented towards humanity.